Parental alienation in legal proceedings: a documentary research project - Mastroianni, Fabio de Carvalho; Freitas Vellosa, Fatima Regina de; Moyano Malara, Livia Colazante; Castro Leao, Andreza Marques de [UNESP] (Univ Federal Fluminense, Inst Ciencias Humanas & Filosofia, 2019)
Parental alienation has been widely discussed in Brazil over the past decade, culminating in the creation of specific legislation (law no. 12.318/2010). This article seeks to explore how this subject has been discussed by the judiciary and specialized teams by conducting a documentary analysis of legal cases, in what constitutes a descriptive, exploratory, and analytical study. 80 lawsuits have been consulted from the family courts in the district of Araraquara (Sao Paulo), all filed in 2015. Of these, 17 touch on the subject, with none of the specialist studies (in the field of Psychology and Social Services) confirming the practices or seeking to provide subsidies to identify the alienator and the alienated. On the contrary, the reports have prioritized resolving the conflict and the importance of parents and children living together. It may be concluded that the way in which the legislation approaches the subject - aiming to identify the practices of parental alienation - may prove counterproductive, further exacerbating conflicts and failing to understand the parties involved in the process (father-mother) as figures fundamental to their children's development, prompting the need for further reflection and debate.
Keywords: Legal psychology; parental alienation; psychosocial assessment; Family Law